1987
DOI: 10.1161/01.cir.75.3.627
|View full text |Cite
|
Sign up to set email alerts
|

Protection against atherogenesis with the polymer drag-reducing agent Separan AP-30.

Abstract: The inhibitory effect of Separan AP-30, an anionic polyacrylamide, on atherosclerotic plaque formation in aortas of rabbits on a high (2%) cholesterol diet was tested over a period extending from 37 to 170 days. Atherogenesis was quantified morphometrically by application of a computerassisted image analysis of histologic cross sections of the aorta. The area of vessel wall-atheroma interface, fraction of lumen occluded, and other indexes of atherogenesis were measured in each of 26 segments of aorta excised f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 35 publications
0
29
0
Order By: Relevance
“…13 Previous studies have demonstrated that intravenous injection of even nanomolar concentration of DRPs increased hemodynamic shear stress 14,15 and decreased peripheral vascular resistance. 16 In this study, we hypothesized that intravenous infusion of DRPs may improve left ventricular hypertrophy and aortic remodeling in spontaneously hypertensive rats (SHR) through increasing blood shear stress.…”
Section: Zhang Et Almentioning
confidence: 99%
“…13 Previous studies have demonstrated that intravenous injection of even nanomolar concentration of DRPs increased hemodynamic shear stress 14,15 and decreased peripheral vascular resistance. 16 In this study, we hypothesized that intravenous infusion of DRPs may improve left ventricular hypertrophy and aortic remodeling in spontaneously hypertensive rats (SHR) through increasing blood shear stress.…”
Section: Zhang Et Almentioning
confidence: 99%
“…These polymers have been investigated and used for various industrial and engineering applications including crude oil transport through pipelines, firefighting, and reducing drag on ships and submarines (16). When applied to animal models of atherosclerotic plaque these polymers showed beneficial hemodynamic effects including delay/prevention of the development of atherosclerosis in animals kept on an atherogenic diet (8). The literature has reported that DRP are described as long-chain polymers with a molecular weight above 1,000,000 Da (10).…”
Section: Discussionmentioning
confidence: 99%
“…Classically, the polymer-induced drag-reducing effect occurs in turbulent flows, even though some studies have also described this effect on pulsatile flows in straight and spiral pipes or in Couette flows with Taylor vortices at low Reynolds numbers (6,7). There are results showing that atherosclerotic plaque formation in aortas from rabbits submitted to a high cholesterol diet was reduced by using the polymer Separan AP-30 (8). In addition, the administration of small amounts of DRP may decrease atherosclerosis by increasing shear stress in areas normally exposed to low shear stress (9).…”
Section: Introductionmentioning
confidence: 99%
“…These studies were originally motivated by the knowledge that small amounts of long-chain polymer additives-"drag-reducing polymers" (DRPs) -can dramatically reduce drag in turbulent flows while having negligible effect on laminar flows [94]. Studies with laboratory animals indicate that the addition of DRPs to blood leads to many beneficial effects, including (1) reduced atherosclerotic plaque deposition ( Figure 11.3(a)) [90,95]; (2) increased cardiac output [96] and reduced severity of cardiac stenosis or myocardial infarction [97][98][99][100]; (3) improved survival probability after severe hemorrhage with use of polymer-containing resuscitation fluids [91,93,101] (see Fig. 11.3(b)); (4) reduced immune attack of implanted polymeric tissue scaffolds [92] (see Fig.…”
Section: Effect Of Plasma Rheology On Cell Distributionmentioning
confidence: 99%
“…Experiments in microfluidic devices [93,105] have shown that the addition of a small amount of DRPs to suspension of RBCs results in a redistribution of RBCs with a significant reduction in the [90]. (b) Survival vs. time for rats subjected to hemorrhage and not treated (CON), treated by injection of normal saline (NS) or intravenously injected with saline containing a drag-reducing polymer [91].…”
Section: Effect Of Plasma Rheology On Cell Distributionmentioning
confidence: 99%